Signifikansi Peran Sektor UMKM Dalam Meningkatkan Ekspor - Visca Amaratya; Nur Afiyati (Lembaga Pengembangan Kinerja Dosen, 2024)
Even though MSME business performance has not reached its optimal potential due to various obstacles such as lack of capital support and obstacles in business management, attention to the MSME sector remains important and growing. The three main reasons for supporting the increase in MSMEs are: first, MSMEs act as a survival strategy in times of economic downturn; second, the tendency of MSMEs to absorb labor and intensively utilize local natural resources; third, the role of MSMEs in reducing poverty levels and encouraging income distribution in society.